Challenges and frictions in the implementation of the CEFR-M: a conceptual paper - Ahmad Sukri, Saiful Islam; Zubairi, Ainol Madziah; Saad, Mohammad Azannee; Preece, Abdul Shakour Duncan (Universiti Teknologi MARA, 2025)
Undeniably, there have been a lot of English language educational initiatives inMalaysia since 1970, mainly aimed at improving learners’ English language skills. The most recent development is the incorporation of the Common European Framework of Reference for Languages (CEFR) into Malaysian English language curricula, also known as CEFR-M at all levels of education from pre-school to university. This move is in line with the country’s long-term commitment to raise the bar for students’ English proficiency, as articulated in the Malaysian Education Roadmap 2013-2025 and further accentuated in the 10-year Reform of English Language Education in Malaysia: The Roadmap 2015-2025. The implementation of the CEFR has entered the final phase of reform and has not been without challenges and frictions since its official introduction to primary and secondary education in 2017. Drawing upon numerous studies backed up by CEFR-related webinars, national CEFR-related English examination reports and CEFR-related documents pertinent to the CEFR implementation in Malaysia, this paper aims to bring to the fore the challenges encountered in the implementation of the CEFR in the local context, which may reverberate with similar problems in other countries pursuing the same educational agenda. The paper ends with implications worth reflecting upon to better manage and improve the CEFR-M implementation.